DECOMPOSING THE SOCIOECONOMIC INEQUALITY IN UTILIZATION OF MATERNAL HEALTH CARE SERVICES IN SELECTED COUNTRIES OF SOUTH ASIA AND SUB-SAHARAN AFRICA. Issue 6 (30th October 2017) - Goli, Srinivas; Nawal, Dipty; Rammohan, Anu; Sekher, T. V.; Singh, Deepshikha
Summary: The gap in access to maternal health care services is a challenge of an unequal world. In 2015, each day about 830 women died due to complications of pregnancy and childbirth. Almost all of these deaths occurred in low-resource settings, and most could have been prevented. This study quantified the contributions of the socioeconomic determinants of inequality to the utilization of maternal health care services in four countries in diverse geographical and cultural settings: Bangladesh, Ethiopia, Nepal and Zimbabwe. Data from the 2010–11 Demographic and Health Surveys of the four countries were used, and methods developed by Wagstaff and colleagues for decomposing socioeconomic inequalities in health were applied. The results showed that although the Concentration Index (CI) was negative for the selected indicators, meaning maternal health care was poorer among lower socioeconomic status groups, the level of CI varied across the different countries for the same outcome indicator: CI of −0.1147, −0.1146, −0.2859 and −0.0638 for <3 antenatal care visits; CI of −0.1338, −0.0925, −0.1960 and −0.2531 for non-institutional delivery; and CI of −0.1153, −0.0370, −0.1817 and −0.0577 for no postnatal care within 2 days of delivery for Bangladesh, Ethiopia, Nepal and Zimbabwe, respectively. The marginal effects suggested that the strength of the association between the outcome and explanatory factors varied across the different countries. Decomposition estimates revealed that the key contributing factors for socioeconomic inequalities in maternal health care varied across the selected countries. The findings are significant for a global understanding of the various determinants of maternal health care use in high-maternal-mortality settings in different geographical and socio-cultural contexts.